Construindo o ser professor: a experiência como constituinte de trajetórias histórico-profissionais (dos anos 60 aos anos 90) - Silva, Lilian Calaça da (2003)
This study aims a reflection on the knowledge of life experiences as constituents of the teachers’ historic-professional and extra-professional path, whom act in the 60’s, in some levels, since the Elementary School and, along the 80’s, started to work at the Federal University of Uberlândia, where they have being acting in many education courses till retire in the first half of the 90’s. Understanding the teacher’s formation doesn’t deplete in the organized knowledge, we search through this study to recover this docents’ rule, stressing the importance to think about this formation not only from the professional and organizational development, but mainly on the knowledge’s formation and construction. First, was made a revision of the main studies about experience, docent knowledge and memory, balancing by its conceptual and methodological support, produced from distinct theoretician-pedagogical approaches on the being teacher. From the oral narratives, written an in a context, of a five teachers group, a reflection was produced about how did they constitute themselves as teachers. Was proved that the institutionalized teacher formation is not worthless in any school level, but there are knowledge constituted by the teachers which are result of his professional and extra-professional experiences. The related experiences are also condition to feed the reflection and the school practice on the teacher’s formation, constructed not only by their formal formation in university, but also from the knowledge created by themselves as by their experiences. The study reveals that the teachers construct and reconstruct, permanently, their different knowledge, their experiences and utopias. Therefore, the experience is a dimension among others. Elect it this way is contemplate the related formation, in other aspect to be considered, must be composed in a unilateral perspective. Therefore, the docent experience can’t be placed in the school education stage, as its rescuer, as unilaterally promoter of the overcoming of the school education’s sequel.